Electronic journal of biotechnology EJB. (Universidad Católica de Valparaíso and CONICYT, 1997)
International scientific electronic journal covering all areas related to biotechnology, from molecular biology and the chemistry of biological process to aquatic and earth environmental aspects, as well as computational applications and policy issues.